The strange death of Pagan Rome: reflections on a historiographical controversy - Lizzi Testa, Rita (Giornale italiano di filologia, 2013)
Addressing the problem of the relationship between pagans and Christians cannot be separated from assessing the nature of the relationship that linked or divided the members of two very different religions. Te model of conflict has been disseminated by the Hungarian scholar András Alföldi, who in 1934 presented a Christian Constantine in irreconcilable conflict with a pagan Rome and later (most notably in 1958, in a seminar conference at the Warburg Institute) consolidated the idea of a conflictual model in which the aristocracy of Rome, faced with a tightening of measures against traditional cults, realized a real "pagan revival", to raise against Teodosius I "the last pagan army of the ancient world". This model was subjected to a massive critique by Alan Cameron ('The Last Pagans of Rome', Oxford 2011), but was powerfully restated by Stéphane Ratti ('Polémique entre pai͏̈ens et chrétiens. Histoire', Paris 2012). The debate, then, in the course of less than a year, has gained new, effervescent relevance
Keywords: Aufsatzsammlung; Untergang; Heidentum; Römisches Reich